Hubungan Lama Bekerja Dengan Keluhan Low Back Pain Pada Perawat Rumah Sakit Islam Muhammadiyah Kendal - NUGRAHA, ARFIAN EKA; , Totok Budi Satoso, M.PH; , Wahyuni, M.Kes (2015)
Background: Health and safety at work or K3 is integral in the system of employment and human resources. Therefore, health and safety at this time is not only an obligation that must be met by the workers, but also must be met by a system of work, including the profession as a nurse. Objective: This study aimed to long working relationship with complaints of low back pain in hospital nurses Islam Muhammadiyah Kendal. Methods: This study is a systematic observation with preliminary participant observation for the discovery and formulation of the problem to be targeted observation using cross sectional method. Samples of 60 people were taken through purposive sampling method, measurement in the study using the Visual Analogue Scale (VAS) to measure the value of silent pain, motion and press. Results: From the test result of correlative Chi-Square test to get the p <0.05, indicating a long working relationship with complaints of low back pain in hospital nurses Islam Muhammadiyah Kendal. Conclusion: There is a long working relationship with complaints of low back pain in hospital nurses Islam Muhammadiyah Kendal